Importancia de los abonos orgánicos en el cultivo de cacao - Cabero Apraez, Deivis Ulises (2024)
The current case study based on the importance of organic fertilizers in cocoa cultivation, in which the objective was determined to describe the importance of organic fertilizers in cocoa cultivation. As for the methodology, it was based on a qualitative study with a descriptive approach in which it was developed through the collection of all types of information, carrying out a detailed investigation on the different free access web pages, scientific articles, degree theses, sources and bibliographic documentation available on different digital platforms. In the results, the detailed evaluation of various compost sources revealed that the compost made from cocoa shells presents high efficiency as an organic fertilizer for cocoa cultivation, this compost not only provides essential nutrients, but also improves retention of water and soil structure. In conclusion, the adaptability of these fertilizers to the different stages of cocoa development demonstrates their positive impact on the performance of trees and cocoa production. Organic fertilizers not only supply essential nutrients, but also contribute to improving the structure of the cocoa. soil and suppress weeds.